PENGARUH INDEPENDENSI, KECERDASAN SPRITUAL DAN ETHICAL SENSITIVITY TERHADAP KUALITAS AUDIT PEMERINTAH DENGAN INTEGRITAS AUDITOR SEBAGAI VARIABEL MODERASI - Farid Fajrin (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine how the influence of independence, spiritual intelligence, and ethical sensitivity on audit quality, and how the influence of independence, spiritual intelligence, and ethical sensitivity on audit quality moderated by auditor integrity at the Inspectorate of South Sulawesi Province. The results showed that spiritual intelligence and ethical sensitivity had a positive and significant effect on audit quality, while independence had a positive but not significant effect on audit quality. Auditor integrity is able to strengthen the influence of spiritual intelligence and ethical sensitivity on audit quality but weakens the influence of independence on audit quality. Further research can use broader research object and applying mix method for better result. Keywords: Auditor, Ethical Sensitivity, Independency, Integrity, Spiritual Quetiont.